Strength imbalances and prevention of hamstring injury in professional soccer players: A prospective study - Croisier, J. L.; Ganteaume, S.; Binet, J.; Genty, M.; Ferret, J. M. (The American Journal of Sports Medicine, 2008)
The relationship between muscle injury and strength disorders remains a matter of controversy.